2009
DOI: 10.1038/nature07845
|View full text |Cite
|
Sign up to set email alerts
|

High-frequency modification of plant genes using engineered zinc-finger nucleases

Abstract: An efficient method for making directed DNA sequence modifications to plant genes (gene targeting) is presently lacking, thereby frustrating efforts to dissect plant gene function and engineer crop plants that better produce the world's burgeoning need for food, fiber and fuel. Zinc finger nucleases (ZFNs) - enzymes engineered to create DNA double strand breaks at specific loci - are potent stimulators of gene targeting,1,2 including at engineered reporter genes in plants.3,4 Here we demonstrate high frequency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
460
0
7

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 669 publications
(476 citation statements)
references
References 18 publications
9
460
0
7
Order By: Relevance
“…1 Two of the three reports cited provide data that enable calculation of failure rates for modular assembly. 2,3 Although it is true that modular assembly yielded ZFNs for ~25% of the DNA sites targeted, failure rates measured instead by the number of zinc finger proteins tested are remarkably consistent with those reported in our original Correspondence. 1 For example, at the human CCR5 gene, Kim et al screened 315 pairs of ZFNs for activity; 3 this large-scale effort yielded only a small number of functional ZFN pairs (93.3% failure rate for ZFN pairs tested).…”
Section: To the Editorsupporting
confidence: 74%
See 1 more Smart Citation
“…1 Two of the three reports cited provide data that enable calculation of failure rates for modular assembly. 2,3 Although it is true that modular assembly yielded ZFNs for ~25% of the DNA sites targeted, failure rates measured instead by the number of zinc finger proteins tested are remarkably consistent with those reported in our original Correspondence. 1 For example, at the human CCR5 gene, Kim et al screened 315 pairs of ZFNs for activity; 3 this large-scale effort yielded only a small number of functional ZFN pairs (93.3% failure rate for ZFN pairs tested).…”
Section: To the Editorsupporting
confidence: 74%
“…1 For example, at the human CCR5 gene, Kim et al screened 315 pairs of ZFNs for activity; 3 this large-scale effort yielded only a small number of functional ZFN pairs (93.3% failure rate for ZFN pairs tested). Similarly, for the tobacco SuRB gene, 2 we tested 32 zinc finger arrays in vitro but identified only three with functional activity (91.6% failure rate for zinc finger arrays tested). These data are consistent with our original predicted failure rates of ~94% and ~76% for modularly assembled ZFN pairs and zinc finger arrays, respectively.…”
Section: To the Editormentioning
confidence: 99%
“…In many cases, ZFN-mediated DSBs have been used to stimulate the HR DNA-repair machinery for HR-mediated gene replacement and gene addition. This approach has been successfully implemented in animals (Beumer et al, 2006;Meng et al, 2008), human cell lines (Urnov et al, 2005;Lombardo et al, 2007), and plants (Wright et al, 2005;Cai et al, 2009;Shukla et al, 2009;Townsend et al, 2009;de Pater et al, 2013). However, it is important to note that while ZFNinduced DSBs can indeed induce the HR repair machinery, most of these breaks are repaired by the cell's NHEJ DNA-repair machinery in plant and other species.…”
mentioning
confidence: 99%
“…This allows researchers to put the new gene in a spot in the genome where its expression is optimal, and reduces the risk of disrupting the plant's genome in undesirable ways. Voytas's group has already shown that tobacco plants can be modified with ZFNs to introduce herbicide resistance 1 . Other groups have added herbicide resistance to maize (corn) with ZFNs 2 or have used TALENs to snip out the gene in rice that confers susceptibility to bacterial blight 3 .…”
Section: Advanced Techniquesmentioning
confidence: 99%